Wstęp do psychologii miłości - Błaszczyk, Marek (Człowiek i Społeczeństwo, 2021)
The paper presents a critical approach to Psychologia kochania by Piotr Olesiński (Warszawa 2018). It discusses the main theses presented in the dissertation and invites to reflection focused on the psychological dimension of love, its role and place in human existence.